Immune cell aberrations in Systemic Lupus Erythematosus: navigating the targeted therapies toward precision management - YuXian Wu; Wangzheqi Zhang; Yan Liao; Ting Sun; Yang Liu; Yaoyang Liu (Cellular & Molecular Biology Letters)
Abstract Systemic lupus erythematosus (SLE) is a complex autoimmune disease characterized by multilayered dysregulation of immune cell homeostasis, spanning B cell effector dysfunction, T follicular helper (Tfh) cell hyperactivity, and plasmacytoid dendritic cell (pDC) tolerance breakdown. Advances in high-parameter immunophenotyping, single-cell multiomics profiling, and spatial multiomics have redefined SLE pathogenesis, revealing stage-specific immune network perturbations. These discoveries have propelled mechanism-driven therapeutic strategies, including CD19-targeted chimeric antigen receptor T cell (CAR-T) therapy for B cell depletion, disruption of T–B cell synaptic signaling (CD40L inhibitors), and restoration of pDC tolerance (anti-BDCA2 antibodies). While patient heterogeneity poses challenges for universal therapeutic efficacy, emerging strategies integrating molecular endotyping and cellular biomarkers hold promise for overcoming these limitations. By aligning targeted therapies with the immunophenotypic signatures of individual patients, precision medicine approaches are expected to optimize treatment efficacy, minimize off-target effects, and ultimately enhance long-term clinical outcomes in SLE. This review synthesizes current insights into how immune cell perturbations contribute to SLE pathogenesis, modulate disease flares, and determine therapeutic refractoriness, with a critical synthesis of recent clinical trial outcomes.